IMPLEMENTASI MODEL CIPP PADA PEMBELAJARAN IPS PROGRAM MERDEKA BELAJAR DI SEKOLAH DASAR NEGERI DONOMULYO - Wahyu Sudibyo; Esti Setiawati (Jurnal Sosialita, 2026)
This study aims to provide a detailed explanation of the evaluation results of the Merdeka Belajar (Freedom to Learn) program in Social Studies (IPS) learning using a descriptive qualitative approach through the implementation of the CIPP evaluation model at SD Negeri Donomulyo. The research subjects consisted of teachers and students from grade III and grade IV, involving 2 teachers, 28 students in grade III, and 28 students in grade IV. Data were collected through observation and document analysis. The findings of the study show that: 1) The evaluation of curriculum implementation using the CIPP model in Social Studies learning at SD Negeri Donomulyo, Kapanewon Nanggulan, Kulon Progo Regency, has been carried out effectively; 2) In terms of context, the school’s support system, teacher qualifications, and facilities are highly adequate. Regarding input, teacher preparedness, student readiness, curriculum, and learning media strongly support the learning process. In terms of process, Social Studies learning activities have been conducted in accordance with standardized procedures. In terms of product, students’ final examination scores and project-based learning outcomes are highly satisfactory; 3) Classroom interactions, both among students and between teachers and students, have improved the quality of Social Studies learning and yielded positive outcomes not only academically but also in students’ skills in completing projects.